Ethics and CSR: the strategy debate (Confluências | Revista Interdisciplinar de Sociologia e Direito, 2014)
The aim of the paper is to find a link between CSR, ethic and strategy. First we analyze the evolution in the concept of Social Responsibility, the ethical dimension of CSR and the integration of ethics and CSR in the business strategy. In the paper the strategy becomes part of the culture of the economic entity and it is fully integrated into long-term strategy. In the second part of the paper, to better understand the link between CSR, ethic and strategy, we consider two Italian companies that have distinguished themselves for their CSR strategy: Olivetti and Luxottica.